2020
DOI: 10.21106/ijma.405
|View full text |Cite
|
Sign up to set email alerts
|

Expected Surge in Maternal Mortality and Severe Morbidity among African-Americans in the Era of COVID-19 Pandemic

Abstract: Prior to the COVID-19 pandemic, African-American mothers were three times as likely to die from pregnancy-related causes compared to white mothers. The impact of the pandemic among African- Americans could further worsen the racial disparities in maternal mortality (MM) and severe maternal morbidity (SMM). This study aimed to create a theoretical framework delineating the contributors to an expected rise in maternal mortality (MM) and severe maternal morbidity (SMM) among African-Americans in the era of the CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“… 19 The COVID-19 pandemic may further exacerbate these inequities in maternal morbidity and mortality. 20 …”
Section: Discussionmentioning
confidence: 99%
“… 19 The COVID-19 pandemic may further exacerbate these inequities in maternal morbidity and mortality. 20 …”
Section: Discussionmentioning
confidence: 99%
“…6,7 Black maternal pregnancy related morbidity is three times higher than in white mothers. 8 Black men are less likely to carry a diagnosis of coronary heart disease than are white men, and yet are significantly more likely to die from it. The disparities are endless and are at the least tied to a complex combination of access to healthcare and the poorer quality of clinical care that marginalized patients receive.…”
Section: Racism In Healthcarementioning
confidence: 99%
“…Older age (more specifically, over 35), increased body mass index (BMI), and underlying medical illnesses (such as high blood pressure, diabetes, and asthma) are risk factors for severe disease and increased risk of mortality [15,47,[70][71][72]. Also, some studies have observed the effect of African-American and Asian races on increasing the severity of the disease, which still requires further studies to clarify the reliability of the previous findings and subtract the socioeconomic confounding factors [73,74].…”
Section: Critical Care In Pregnant Covid-19 Patientsmentioning
confidence: 99%